Sigma-delta dithering based frequency synthesis and modulation for DCS-1800 - Atasoy, Oğuz. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Today cell phone industry tends to increase the capabilities of the cell phones and at the same time minimize the cost. This trend reflects itself to frequency synthesizer design. Hence, a cheap and efficient way of designing such a frequency synthesizer is suggested in this thesis. The design aims to meet DCS-1800 specifications. The designed frequency synthesizer is based on digital circuits as much as possible. To design such a synthesizer, some different synthesizer and modulation topologies are studied at system level. After deciding on the topology, circuit level design was performed and a full CMOS frequency synthesizer using standard 0.18 μm technology was obtained.
Keywords: Frequency synthesizers.